2000
DOI: 10.1523/jneurosci.20-18-06998.2000
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Anterior Nucleus of the Ansa Lenticularis in Birds as the Homolog of the Mammalian Subthalamic Nucleus

Abstract: In mammals, the subthalamic nucleus (STN) is a glutamatergic diencephalic cell group that develops in the caudal hypothalamus and migrates to a position above the cerebral peduncle. By its input from the external pallidal segment and projection to the internal pallidal segment, STN plays a critical role in basal ganglia functions. Although the basal ganglia in birds is well developed, possesses the same major neuron types as in mammals, and plays a role in movement control similar to that in mammals, it has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 103 publications
7
84
0
Order By: Relevance
“…5E), and receive inputs with a woolly fiber morphology from either SP/DYNcontaining ( Fig. 5A-C) or ENK-containing striatal neurons, as well as a glutamatergic input from the subthalamic nucleus (Reiner et al, 1998a(Reiner et al, , 1999Jiao et al, 2000). In addition, functional evidence points to similarities in electrophysiological properties (Farries and Perkel, 2000).…”
Section: Rationale For Individual Changesmentioning
confidence: 95%
See 2 more Smart Citations
“…5E), and receive inputs with a woolly fiber morphology from either SP/DYNcontaining ( Fig. 5A-C) or ENK-containing striatal neurons, as well as a glutamatergic input from the subthalamic nucleus (Reiner et al, 1998a(Reiner et al, , 1999Jiao et al, 2000). In addition, functional evidence points to similarities in electrophysiological properties (Farries and Perkel, 2000).…”
Section: Rationale For Individual Changesmentioning
confidence: 95%
“…Subsequent studies (Brauth et al, 1978;Reiner, 1995, 1997;Reiner et al, 1998a), culminating with Jiao et al (2000), revealed the avian ALa to be a glutamatergic cell group that develops within the same prosencephalic region, is located in the same final adult position as the mammalian subthalamic nucleus, and is reciprocally connected with the pallidal part of the basal ganglia. In terms of its function, the neurotransmitters utilized by its inputs and outputs, its developmental profile, its position in the diencephalon, and its likely presence in reptiles, the ALa clearly appears homologous to the subthalamic nucleus of mammals (Reiner et al, 1998a;Jiao et al, 2000) . For this reason, the Forum concluded that the avian ALa should be renamed the subthalamic nucleus (STN; Table 1, Fig.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The avian STh is clearly an homolog of the mammalian nucleus of the same name (Jiao et al, 2000). STh originates from the retromammillary pouch, and its cells migrate dorsally briefly .…”
Section: Subpalliummentioning
confidence: 99%
“…The indirect pathway projects via globus pallidus externallike (GPe) neurons to the subthalamic nucleus which in turn projects to globus pallidus internal-like (GPi) neurons, to the substantia nigra pars reticulata (SNr) and to a pretectal nucleus called spiriformis lateralis (SpL). The projections to GPi and SNr increase inhibition on the motor thalamus and therefore have a net inhibitory effect on movements (Jiao et al, 2000). In the direct pathway, the striatum directly projects to GPi, SNr and SpL.…”
Section: Introductionmentioning
confidence: 99%